Initial uplift of the Tibetan Plateau and environmental implications - Ge, Xiaohong; Ren, Shoumai; Liu, Yongjiang; Ma, Lixiang (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.142